2002
DOI: 10.1021/jf020472s
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of (Z,E)-5,7-Dodecadienol and (E,Z)-10,12-Hexadecadienol, Lepidoptera Pheromone Components, via Zinc Reduction of Enyne Precursors. Test of Pheromone Efficacy against the Siberian Moth

Abstract: Efficient syntheses of (Z,E)-5,7-dodecadienol, a pheromone component of the Siberian moth, Dendrolimus superans sibiricus, and (E,Z)-10,12-hexadecadienol, a pheromone component of various Lepidoptera pheromones, were accomplished by cis reduction of the corresponding enynols with activated zinc. The most energetic reagent was zinc galvanized with copper and silver (Zn/Cu/Ag) that achieved rapid and high-yield reduction in methanol-water. The stereoselectivity of semi-hydrogenation was > or =98%. A process wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Bercot et al employed selective catalytic hydrogenation, generally using a Lindlar catalyst [34], but the pretreatment of calcium carbonate carriers is rarely reported. Khrimian et al first employed zinc activated with copper and silver in cis reduction of the conjugated trienynes in pheromone synthesis [35]. Unfortunately, pretreatment of the active Zn reagent is complicated and time-consuming.…”
Section: Resultsmentioning
confidence: 99%
“…Bercot et al employed selective catalytic hydrogenation, generally using a Lindlar catalyst [34], but the pretreatment of calcium carbonate carriers is rarely reported. Khrimian et al first employed zinc activated with copper and silver in cis reduction of the conjugated trienynes in pheromone synthesis [35]. Unfortunately, pretreatment of the active Zn reagent is complicated and time-consuming.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that Z5,E7-12:OH in D. superans female gland extracts did not elicit responses from antennae of male moths, coupled with the observations from field tests, suggests that this compound may be a precursor to the aldehyde pheromone component (e.g., Teal & Tumlinson, 1986). Furthermore, the trapping efficiency of the Siberian moth pheromone lures loaded with 2 mg of a 1:1 blend of Z5,E7-12:Ald, and Z5,E7-12:OH was reported to decrease significantly after aging in the laboratory for 2 weeks (Khrimian et al, 2002), and those authors suggested that lures should be replaced at intervals of less than 2 weeks. In a dose-response trial, trap captures with 3000 µg dosages were significantly higher than those for doses of 120 and 24 µg, but not for a 600-µg dose (one-way ANOVA, P≤0.05; n = 3).…”
Section: Discussionmentioning
confidence: 95%
“…The reduced activity of the pheromone traps reported here may be due to higher volatility or greater instability of Z5,E7-12:Ald than that of the analogs, alcohol, acetate, or propionate. Furthermore, the trapping efficiency of the Siberian moth pheromone lures loaded with 2 mg of a 1:1 blend of Z5,E7-12:Ald, and Z5,E7-12:OH was reported to decrease significantly after aging in the laboratory for 2 weeks (Khrimian et al, 2002), and those authors suggested that lures should be replaced at intervals of less than 2 weeks. Consequently, we suggest that lures loaded with 1 mg of Z5,E7-12:Ald be replaced at intervals of 10 days until more long lasting formulations can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Partial cis-hydrogenation of 12 was accomplished in 80% yield and O98% stereoselectivity using a Zn(Cu/Ag) reagent that proved handy in the reduction of enynols. 25 Dienol 13 underwent in situ MnO 2 oxidation-Wittig reaction similar to 9 and furnished esters 14 and 15 in 59 and 3% yields, respectively. Ester 15 was 93% pure and was contaminated with esters 7 and 14, and ester 14 was 96% pure by GC.…”
Section: Synthesis Of 4z Isomersmentioning
confidence: 99%